PENGARUH DAUR HIDUP PERUSAHAAN TERHADAP KEPUTUSAN STRUKTUR MODAL - Zaenal Arifin (Universitas Trisakti, 2009)
This research investigate the effect of corporate life cycles on capital structure decision and analyze whether capital structure that considering corporate life cycles influence the company's performance. Using manufacturing companies that listing in Jakarta Stock Exchange in 2006 this research found that : (1) corporate life cycle influence capital structure decision only in the big-size companies. The big-size firms use larger debt ratio when the companies enter into growth level of life cycle; (2) capital structure decision that considering corporate life cycles do influence the company's performance, when using cumulative abnormal return as a proxy of company's performance.In the big-size firms, the stockholders give negafive reaction to the increase of debt in the pioneering level of life cycles. In the medium-size firms, the stockholders give positive response to the increase of debt in the mature level of life cycles. In the small-size firms, the stockholders give positive response to the increase of debt in the growth level of life cycles. Capital structure decision that considering corporate life cycles do not influence the company's performance, when using return on investment as a proxy of company's performance. Keywords : Capital structure, Corporate life cycles, Firm-size, Firm performance